Overcoming challenges to enable targeting of metastatic breast cancer tumour microenvironment with nano-therapeutics: Current status and future perspectives - Karishma Niveria; Monika Yadav; Kapil Dangi; Anita Kamra Verma (OpenNano, 2022)
Tumour-microenvironment (TME) comprising of impenetrable inter-communications among stromal cells, tumour cells, cancer-associated blood and lymphatic vessels, pericytes, cancer-associated-fibroblasts, cancer-stem cells and extracellular matrix (ECM) that can substantially impact the onset, spread and progression of cancer metastasis. Metastatic breast-cancer remains the most elusive, incurable form of cancer. This necessitates an in-depth understanding and optimization of innovative nano-drug delivery platforms that exploit the metastatic TME targeting individual cellular components. Stimuli-sensitive nanoparticles (NPs) can enhance spatiotemporal control over cell-targeting. Nano-therapies require to be safe, effective and scalable in production for translation to clinics. In-divergence to conventional therapies that promote widespread ablation, emerging nano-strategies specifically modulate the varied cell populations of TME such as targeting pericytes and endothelial cells for vascular normalization. Further, we outline the lacuna in the current nanotherapeutics strategies and highlight the novel perspectives on design of pre-clinical and clinical trials to modulate the breast-cancer metastasis to hasten clinical translation.